Prospects and Opportunities of 2D van der Waals Magnetic Systems. Issue 5 (31st March 2020) - Wang, Meng‐Chien; Huang, Che‐Chun; Cheung, Chi‐Ho; Chen, Chih‐Yu; Tan, Seng Ghee; Huang, Tsung‐Wei; Zhao, Yue; Zhao, Yanfeng; Wu, Gang; Feng, Yuan‐Ping; Wu, Han‐Chun; Chang, Ching‐Ray
Abstract: The existence of spontaneous magnetization in low dimensional magnetic systems has attracted intensive studies since the early 60s and research remains very active even now. Only recently, magnetic van der Waals (vdW) systems down to a few layers have been broadly discussed for their magnetic order ground states at finite temperature. The naturally inherited layered structure of the vdW magnetic systems possessing onsite magnetic anisotropy from band electrons can suppress the long‐range fluctuations. This provides an excellent vehicle to study the transition of magnetism to 2D limits both theoretically and experimentally. Here the current status of 2D vdW magnetic system and its potential applications are briefly summarized and discussed. Abstract : Recently, magnetic van der Waals (vdW) systems down to the single layer limit have been studied intensively. Herein, the current status of 2D vdW magnetic systems is summarized from both a theoretical and an experimental point of view. The fundamental physics of 2D magnetism are discussed, along with the future outlook and potential applications of 2D vdW magnetic systems.